ERAAP modulation: A possible novel strategy for cancer immunotherapy? - Fruci, Doriana (Landes Bioscience, 2012)
Recent findings demonstrate that loss of ERAAP, an endoplasmic reticulum aminopeptidase involved in antigen processing, plays a key role in stimulating anti-tumor innate and adaptive immune responses. We show that MHC class I molecules produced in the absence of ERAAP retain their capability of presenting antigens to CD8+ T cells, but not of inhibiting NK cells.